2012
DOI: 10.2105/ajph.2011.300515
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Aerobic Fitness and Academic Achievement: A Longitudinal Examination of Students During Their Fifth and Seventh Grade Years

Abstract: Students' aerobic capacity is associated with greater academic achievement as defined by standardized test scores. This advantage appears to be maintained over time, especially if the student stays in the HFZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 25 publications
12
80
1
3
Order By: Relevance
“…8,10,11,27 Specifically, in this study, higher aerobic fitness mediated the positive association of selfreported PA and AA among all children. Interestingly, among girls, the direct association between self-reported PA and AA remained after the mediator aerobic fitness was added to the model but disappeared among boys.…”
Section: Jpah Vol 15 No 2 2018supporting
confidence: 48%
“…8,10,11,27 Specifically, in this study, higher aerobic fitness mediated the positive association of selfreported PA and AA among all children. Interestingly, among girls, the direct association between self-reported PA and AA remained after the mediator aerobic fitness was added to the model but disappeared among boys.…”
Section: Jpah Vol 15 No 2 2018supporting
confidence: 48%
“…Fitness was consistently associated with academic achievement across the three longitudinal studies (107, 150, 166). Sample sizes across the studies ranged from 757 to 1725, and the participants involved ranged from 2 nd through 7 th grade.…”
Section: Resultsmentioning
confidence: 93%
“…All three studies used the FITNESSGRAM® to assess fitness level. One study used the WESTEST (166), one used a California standardized test in math and English , and one study used tests of literacy and numeracy designed by Australian government education authority and the Australian Curriculum, Assessment and Reporting Authority (150). The studies showed that students who increased their fitness or maintained fitness across time had higher academic achievement scores than students who did not achieve the Healthy Fitness Zone® (the gender- and age-specific fitness goals) on the physical fitness tests that are part of the FITNESSGRAM™ (107, 166), and that students and schools with higher fitness levels had achieved better literacy and numeracy scores (150).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other outcomes besides metabolic syndrome should be evaluated because physical fitness is associated with more than just cardiometabolic risk. For example, recent research has shown the HFZ to be related to risk for depression (Rieck, Jackson, Martin, Petrie, & Greenleaf, 2013), blood markers of nonalcoholic fatty liver disease (Trilk et al, 2013), academic achievement (Wittberg, Northrup, & Cottrell, 2012), and cognitive control (Scudder et al, 2014).…”
Section: S17mentioning
confidence: 99%